Balancing the energy equation for healthy kidneys1. Issue 4 (10th September 2015) - Mount, Peter F; Power, David A
Abstract: The high‐energy requirement of the kidney and the importance of energy metabolism in renal physiology has been appreciated for decades, but only recently has there emerged a strong link between impaired renal energy metabolism and chronic kidney disease (CKD). The mechanisms underlying the association between changes in energy metabolism and progression of CKD, however, remain poorly understood. A new study from Qiu and colleagues reported in the Journal of Pathology has advanced this understanding by showing that, after renal injury, the energy sensor AMPK inhibits epithelial–mesenchymal transition and inflammation, processes important in the pathogenesis of CKD. Furthermore, this study identifies an interaction between AMPK and CK2β as an important mechanism in the anti‐fibrotic effect. CK2β has previously been shown to interact with STK11 (also known as LKB1) to regulate cellular polarity. These findings are consistent with the known roles of the LKB1–AMPK pathway in sustaining cellular energy homeostasis and epithelial cell polarity, and add to growing evidence linking the suppression of energy metabolism to CKD. They emphasize the importance of energy metabolism in general and the LKB1–AMPK axis in particular as key investigational and therapeutic targets in the battle against CKD. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.